The Influence of Using Conventional/Lecture Learning Methods on the Achievement of Arabic Writing Skills - Alim Mujahidin; Moh. Abdul Kholik Hasan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Conventional method is a teaching method commonly used by teachers and is called a traditional method, while unconventional method is a teaching method that has just developed and is not commonly used in general such as modules, programmed teaching, unit teaching, machine programs, methods that have just been developed in certain schools that have complete infrastructure and facilities. Arabic or Shad language is one of the most common languages ​​in the Semitic language group, used by Arab world countries in addition to many other regions such as Turkey, Ahwaza, Mali, Chad, Senegal, Ethiopia, Eritrea, Iran, and Sudan. Arabic is considered a sacred language because it is the language of the Qur'an where prayer and other worship in Islam are not performed except with mastery of Arabic. Writing skills are the ability to express thoughts into written language through sentences that are arranged in a complete, complete, and clear manner so that these thoughts can be communicated to the reader successfully.